Using Asset Allocation Strategy in Sharia Equity Mutual Fund to Shape Optimum Portfolio - Vidya Ramadhan Putra Pratama (Journal Research of Social Science, Economics, and Management, 2025)
The swift advancement of the Islamic finance sector has established Islamic equities mutual funds as a significant vehicle for ethical and value-driven investing, particularly in emerging economies such as Indonesia.  Despite its increasing popularity and compliance with Sharia rules, numerous investors in Sharia equity mutual funds predominantly employ a passive portfolio management strategy, which may hinder the complete optimization of risk-return efficiency.  Numerous elements enable an investor to ascertain their success or failure in an investment.  A crucial aspect in an investor's success is the approach employed in asset allocation and portfolio management.  Consequently, investors must strategically allocate investment assets within the portfolio to maximize returns.  This research seeks to investigate the implementation of asset allocation methodologies in the creation of an optimal portfolio for sharia equities mutual funds.  This research will explicitly examine three alternative strategies in asset allocation: lump sum, dollar-cost averaging, and rebalancing.  The rebalancing procedure will occur in three distinct intervals: quarterly, semi-annually, and annually.  Twenty-six actively managed sharia equities mutual funds registered with the OJK from 2018 to 2024 will serve as research samples for the development of an ideal portfolio.  This study will utilize the Sharpe ratio as a fundamental benchmark for assessing portfolio results.  The research findings suggest that the asset allocation strategy employing a lumpsum or buy-and-hold approach yields the optimal investment returns for sharia equities mutual fund investors.  This discovery may serve as a reference for individual investors or investment managers in future investing deliberations.